Observations of the Polarisation of the Anomalous Microwave Emission: A Review. (2nd December 2012) - Rubiño-Martín, J. A.; López-Caraballo, C. H.; Génova-Santos, R.; Rebolo, R.
Abstract : The observational status of the polarisation of the anomalous microwave emission (AME) is reviewed, both for individual compact Galactic regions as well as for the large-scale Galactic emission. There are six Galactic regions with existing polarisation constraints in the relevant range of 10–40 GHz: four dust clouds (Perseus, ρ Ophiuchi, LDN1622, and Pleiades) and two HII regions (LPH96 and the Helix nebula). These constraints are discussed in detail and are complemented by deriving upper limits on the polarisation of the AME for those objects without published WMAP constraints. For the case of large-scale emission, two recent works, based on WMAP data, are reviewed. Currently, the best constraints on the fractional polarisation of the AME, at frequencies near the peak of the emission (i.e., 20–30 GHz), are at the level of ~ 1 % (95.4% confidence level). Finally, we compare these constraints with the predictions of some theoretical AME models and discuss the possible impact of polarised AME on future primordial B-mode experiments.